ENHANCING STUDENTS’ GRAMMAR AND LEXICAL COMPETENCE THROUGH PEER EDITING (Penelitian Tindakan Kelas Pendidikan Bahasa Inggris Semester IV Fakultas Keguruan dan Ilmu Pendidikan Universitas Siliwangi) - Yuyus Saputra (Jurnal Siliwangi: Seri Pendidikan, 2015)
This research aimed at finding whether peer editing can enhance: (1) grammar and lexical competence in writing class of the first grade students of English Department of Siliwangi University whereas many students still have scores under minimum criteria accomplishment; and (2) to investigate the strengths and the weaknesses of peer editing applied in writing class whereas there are some technique used but they do not make any good solution. The method used in this research was classroom action research and was conducted in three cycles from April 5th until June 1st 2014.The procedures included identifying problem and planning, implementing action, observing, and reflecting. Data of the research was analysed through two kinds of analysing data. Quantitave data was analysed using descriptive statistics while qualitative one was analysed through the following steps, data reduction, data display, drawing conclusion and verification. The results of all cycles conducted as follows; In cycle I, the average score of grammar was 36 , lexical competence was 36.In cycle II it became 40 for grammar, 39 for lexical competence. In the cycle III it became 41 for grammar, 41 for lexical competence. Other findings show that the strenghts of peer editing when it is implemented in writing class, was the students gain independence and  it is less threatening than teacher feedback. However, the weaknesses of the technique are, some students are too polite to correct their friends’ work, feel inferior to  his/her peers, different level of their knowledge that causes different quality of  each editing result such as making errors in correcting.